Pelatihan Budidaya Teripang Kepada Guru Penggerak Sekolah Menengah Kejuruan - TOMATALA, PITJONT (LOSARI DIGITAL, 2025)
Pasca the designation of Tual City as a Cultivation Fisheries Village with sea cucumbers as its commodity by the Ministry of Maritime Affairs and Fisheries - Republic of Indonesia, all elements of society were moved to strive for sea cucumber cultivation. This is also what the Tual City Vocational High School did for the Teacher Mover by conducting a sea cucumber cultivation workshop. This activity aims to transfer knowledge and technology for cultivating sea cucumbers to the Teacher Mover so that it can be included in the curriculum and then transferred to the students. The methods used in this activity include outreach, field visits and training in making containers cultivation and rearing sea cucumber. From results of the activity, it was found that the trained Teacher Mover had mastered the knowledge and technology of sea cucumber cultivation, starting from making cultivation containers to sea cucumber rearing techniques. In addition, armed with the knowledge and technology they have mastered, the Teacher Mover have included sea cucumber cultivation in their curriculum and made sea cucumber cultivation a material that is practiced by students as well as being a source of income for the school.